Pengaruh Waktu Setting Bubu terhadap Hasil Tangkapan Rajungan (Portunus pelagicus) di Perairan Tanjung Kait Kabupaten Tangerang, Banten - Muhammad Syalfa Mahraja Saat; Yusrudin Yusrudin; Sumaryam Sumaryam (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
The purpose of this study is to determine the most effective setting time for collapsible crab traps in catching blue swimming crabs (Portunus pelagicus) in the waters of Tanjung Kait, as well as to assess whether the setting time affects the number of crabs caught across three different time periods. The research method used in this study is an experimental method. Experimental research fundamentally aims to test the relationship between cause and effect. This study employs a Randomized Block Design (RBD) with nine repetitions, using three different setting times: morning, noon, and night. The results of this study indicate no significant difference between the three setting times—morning, noon, and night. Although variations in the number of crabs caught at different times were observed, statistical analysis confirms that these differences are not significant. Therefore, blue swimming crab fishers in the waters of Tanjung Kait can use any of these three setting times to achieve effective catches.